Temperature-sensitive biochemical 18 O-fractionation and humidity-dependent attenuation factor are needed to predict δ18 O of cellulose from leaf water in a grassland ecosystem - Hirl, Regina T (The New phytologist, 2021)
© 2020 The Authors New Phytologist © 2020 New Phytologist Trust.